Controlling the speciation and reactivity of carbon-supported gold nanostructures for catalysed acetylene hydrochlorination. Issue 2 (28th November 2018) - Kaiser, Selina K.; Lin, Ronghe; Mitchell, Sharon; Fako, Edvin; Krumeich, Frank; Hauert, Roland; Safonova, Olga V.; Kondratenko, Vita A.; Kondratenko, Evgenii V.; Collins, Sean M.; Midgley, Paul A.; López, Núria; et al.
Abstract : Distinct gold nanostructures on activated and nitrogen-doped carbons are evaluated in acetylene hydrochlorination. Abstract : Carbon-supported gold catalysts have the potential to replace the toxic mercuric chloride-based system applied industrially for acetylene hydrochlorination, a key technology for the manufacture of polyvinyl chloride. However, the design of an optimal catalyst is essentially hindered by the difficulties in assessing the nature of the active site. Herein, we present a platform of carbon supported gold nanostructures at a fixed metal loading, ranging from single atoms of tunable oxidation state and coordination to metallic nanoparticles, by varying the structure of functionalised carbons and use of thermal activation. While on activated carbon particle aggregation occurs progressively above 473 K, on nitrogen-doped carbon gold single atoms exhibit outstanding stability up to temperatures of 1073 K and under reaction conditions. By combining steady-state experiments, density functional theory, and transient mechanistic studies, we assess the relation between the metal speciation, electronic properties, and catalytic activity. The results indicate that the activity of gold-based catalysts correlates with the population of Au(i )Cl single atoms and the reaction follows a Langmuir–Hinshelwood mechanism. Strong interaction with HCl and thermodynamically favoured acetylene activation were identified as the key features of the Au(i )Cl sites that endow their superior catalytic performance in comparison to N-stabilised Au(iii ) counterparts and gold nanoparticles. Finally, we show that the carrier (activated carbon versus nitrogen-doped carbon) does not affect the catalytic response, but determines the deactivation mechanism (gold particle aggregation and pore blockage, respectively), which opens up different options for the development of stable, high-performance hydrochlorination catalysts.